Prediction of Boarding House Rental Prices Using Multiple Linear Regression Method - Mohede, Nadif Rayhan Julio; Rahmat, Basuki; Kartini, Kartini (Peneliti.net, 2024)
Given the significant influx of students to Surabaya, there is a high demand for affordable boarding house rental near universities. One of the issues that arises is figuring out the rent fee set by the landlord.. This study will focus on solving the problem using machine learning with Multiple Linear Regression (MLR) method. This study also focuses on developing a predictive model for temporary housing rental prices around the National Development University